Operational Analysis of Tricycles-for-Hire Services in Puerto Princesa City, Philippines through Exploratory Data Analysis with Household Profiling and Tricycle Internet of Things (IoT) Data - SANCIANGCO, Erris S.; NG, Anne Clarice L.; TIGLAO, Noriel Christopher C.; TOLENTINO, Niki Jon Y. (Journal of the Eastern Asia Society for Transportation Studies, 2024)
The lack of formal and reliable public transport services in developing countries lead to the proliferation of paratransit modes which can be informal and loosely regulated. In Puerto Princesa City, Philippines where tricycles-for-hire dominate the public transportation system of the city, a study was done to determine the on-ground operational characteristics of different tricycle operators using Internet of Things (IoT) devices. The socioeconomic profile of tricycle sector-dependent households was also determined through a Household Profiling Survey. The study revealed that most tricycle driver-headed households belong to the lower-income classes. In terms of tricycle-for-hire operations, the distances for many trips are short, and certain clustering across tricycle operators exists based on their key performance indicators. The results can be shown to policymakers on how to plan service areas or zones for tricycles, and the additional support they can give to increase earnings.